Towards the development of a talent identification and development program for coaches - O'Keeffe, E. E. (2006)
Coach retention is a significant problem for sport at all levels. Coach turnover, especially of talented and experienced coaches, creates a multitude of operational complexities for many sport organisations. The importance of having quality coaches available to assist the development of high performing athletes has been identified by both sports administrators and elite athletes. However, the data indicate that in Australia, coach accreditation rates are decreasing by more than 9% each year (ASC, 2004). Although programs focusing on coach education and pathways have been developed, minimal research has addressed the elements involved in identifying and retaining talented coaches. The first step in developing a coach talent identification and development program is the formulation of a definition of coaching talent. Although definitions of 'talent' exist in the business and sport performance arenas, these are not directly applicable to the sport coaching context. This study used a multi-method approach through the combination of interviews and questionnaires to develop a comprehensive definition of a talented coach. Two research questions were addressed: What are the attributes of a talented coach (and do perceptions of these differ between different stakeholders)? What are the factors that identify a talented coach (and do perceptions of these differ between different stakeholders)? Information gathered from interviews with experienced personnel in sport (seven coaches and administrators and two senior athletes) was transcribed and coded using open, axial and reflective coding. Themes identified in the analysis were incorporated with the literature to inform construction of the Talent in Coaching Questionnaire. The questionnaire consisted of 100 items investigating three separate but related areas: Demographic Intbrmation (10 items); Attributes of a Talented Coach (77 items); and Identification of a Talented Coach (13 items). Within the Attributes of a Talented Coach section, items were allocated six different categories: Background (10 items); Knowledge (1 3 items); Athlete-Coach Interaction (1 1 items); Operational Practices (12 items); Motivation (7 items); and Attributes (24 items). TWO areas were addressed in the Talent Identification section: the populations in which a talented coach could be found (6 items) and the best possible selection methods to identify a talented coach (7 items). Items were answered using a 5-point Likert scale where 1 = strongly disagree and 5 = strongly agree. The Talent in Coaching Questionnaire was piloted with nine experienced sport personnel and 21 high performing athletics coaches to obtain feedback on face validity, ease of understanding and readability prior to delivery to 300 coaches and administrators across Queensland. The sample incorporated beginner, experienced, retired and lapsed coaches fiom individual and team sports at club, state and national levels. Administrators were defined as involved in the coordination of coaching and support services at club, state or national level. Subjects were sourced fiom 38 different sports through their respective State Sporting Organisations. Within the time fiame allowed, 162 questionnaires were received (54% response rate), which included responses fiom 32 different sports. The sample comprised 27.7% female and 72.3% male subjects, 66.7% of whom were over the age of 40. Using SPSS, the data were analyzed through descriptive statistics, reliability and factor analysis, ANOVA, and Chi square. Items and categories were ranked according to the mean score fiom all participants. The top five attributes of a talented coach were considered to be an individual who; is aware of the individual differences among athletes (mean = 4.74), has an enjoyment of coaching (mean = 4.71), is always looking for improvement in his / her coaching (mean = 4-70), is willing to learn (mean = 4-69), and has knowledge of the fundamental skills required for the sport (mean = 4.65). Attributes considered less important in a talented coach were; one who is motivated by money (mean = 1-70), introverted (mean = 2.38), makes the athlete the first priority in life (mean = 2.42), has received awards for coaching (mean = 2.92) and coached as a head coach (mean = 2.40), State coach (mean = 2.96), or National coach (mean = 2.83). Results suggest that a talented coach may be found among those individuals already coaching or retiring athletes and may be effectively identified through observation at training and competition, possibly through the use of a talent scout. Significant differences were found when item scores were compared by age, gender, experience, and qualifications (National Coaching Accreditation Scheme). Female coaches considered nurturing and teaching attributes more important than did males, additionally career stage may affect consideration of the most important attributes. Practical implications and directions for future research are also discussed.